Caracterización de pacientes con embarazo ectópico atendidas en el Hospital Isidro Ayora Loja - Cabrera Quevedo, Katiusca Silvana (2022)
Ectopic pregnancy is a pathology that occurs when the blastocyst implants in a place other than the uterine cavity. Being an obstetric medical emergency, it is necessary to have data that denote the characteristics of this disease, in order to become aware of this condition and implement better preventive measures. The objective of this study was to characterize the patients with ectopic pregnancy treated at the Isidro Ayora Loja Hospital, to know the sociodemographic characteristics, to identify risk factors and the most frequent therapeutic behavior of these patients. It has a retrospective cross-sectional quantitative approach, The research group was focused on all women diagnosed with an ectopic pregnancy (131 cases) at “Isidro Ayora” General Hospital in Loja from January 1st, 2016 to December 31st, 2020; moreover, a form was used as a tool to collect data; Obtaining that the age range that predominates ectopic pregnancy is between 20 to 30 years of age, 72.5% reside in the urban area, 38.9% are students, tubal pregnancy was the most frequent location with 72.5%, The most prevalent risk factors in our study are the beginning of their sexual life before the age of 18 (52.7%), having had two sexual partners (44.3%), tobacco use (20.6%), pathological history such as gonorrhea ( 14.5%), vaginal infections (30.5%) and surgical interventions in the fallopian tubes respectively, the most applied therapeutic conduct was surgery, being fimbriectomy in 44.3%